Russia's economy and regional spillovers - Torbjörn Becker (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2019)
This paper looks at how the Russian economy has developed under the leadership of Putin and how it spills over to its neighbours in the CIS region. It stresses the importance of international oil prices as a determinant of policies and outcomes in Russia and highlights how this has impacted macroeconomic performance during Putin's different terms in office. Although Russia is not an economic superpower globally, the size and importance of Russia for the CIS region is significant and thus oil price changes also drive the economic development of non-fuel exporting CIS countries to a significant degree.
Keywords: E60; F40; O52; 330; Russia; Putin; macroeconomis; CIS; transition